Análise de mesoescala de evento de tempo severo no Rio Grande do Sul através de simulações no modelo WRF - Lopes, Murilo Machado (2024)
Severe convective storms are common in the La Plata Basin during spring, producing frequent hail; however, long-lived supercells are relatively rare in the region. The formation of a long-duration supercell storm during a severe weather event on October 14, 2015, was responsible for damage associated with hail across a wide swath of the central region of Rio Grande do Sul. Despite the presence of other convective cells, the vast majority of severe weather reports from that day was associated with the main storm, which had a long life cycle, lasting more than 8 hours. This work carried out a storm-scale numerical simulation aiming to reproduce the supercellular characteristics of the main storm recorded in the event and to understand the characteristics of the near-storm atmospheric environment that controlled the storm development. Based on initial and boundary conditions from the global Climate Forecast System version 2 (CFSv2) reanalysis, numerical simulations with the non-hydrostatic model WRF (Weather Research and Forecasting) were configured with three spatial domains of 9, 3 and 1 km horizontal grid spacing nested in a two-way mode. In the 1 km domain, the simulation represented well the discrete mode of the convective cell, its long duration, the surface hail accumulation and the typical characteristics of supercells, such as a long trail of a steady rotating updraft. The presence of an intense low level jet contributed to the convective initiation and to the establishment of long and strongly curved hodographs in the shallow layer, which generally favors the tornadic mode instead of intense hail production. Therefore, the meteorological aspects that led to the high number of hail reports were analyzed. An easterly low-level flow, channeled through the Central Depression of Rio Grande do Sul, played na important role in enhancing the vertical wind shear in the shallow layer and also intensifying the storm-relative winds, favoring a long-lived supercell with a wide updraft. This configuration also contributed to a greater curvature of the hodographs at low levels. However, lack of strong streamwise environmental vorticity at levels closest to the surface hampered the intensification of rotation at the low levels of the storm, making hail production the predominant severe weather phenomenon rather than a tornado or intense surface winds.